Wind-resistant design and safety evaluation of cooling towers by reinforcement area criterion. (15th August 2019) - Yu, Miao; Zhao, Lin; Zhan, Yanyan; Cui, Wei; Ge, Yaojun
Highlights: The interference effects under grouped towers are measured by wind tunnel tests. An equivalent internal force weighting criterion based on the reinforcement area is proposed. The internal force weighting criterion can assure both structural safety and economy. Abstract: Wind loads are the predominant loads of all the various loading combinations in structural design of cooling towers. Existing wind loading codes have a basic single interference factor and a simplified two-dimensional static wind pressure distribution formula, and do not enable accurate structural safety/reliability evaluation under dynamic wind loads. Among the various Equivalent Static Wind Loadings (ESWLs), the reinforcement-area-based ESWL is selected in this study, and the extreme reinforcement area considering wind directionality effect and nonuniform circumferential wind pressure is expressed as the equivalent criterion of reinforcement area envelope. A structural safety evaluation method, based on this innovative cooling tower design criterion, is derived as the dynamic reinforcement area envelope concept. The effects of time-variant weighted internal forces and non-Gaussian peak factor for the reinforcement area envelope are considered. The reinforcement area envelopes are compared with those from three different codes based on traditional simplified ESWLs. Finally, the results show that the existing loading codes do not cover the effects of interference amplification for structural safety. An alternative framework based on the reinforcement area criterion of weighted dynamic interval forces and its extreme value envelope are proposed, which can optimize both the economy and the structural safety design of cooling towers.